Epistemic and Linguistic Injustice in Research: Sharing Experiential Knowledge / Injustices épistémiques et linguistiques en recherche : partage de savoirs expérientiels - Drolet, Marie-Josée; Lafond, Valérie; Côté, Louis (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
This article discusses a rarely addressed yet pivotal issue in academia: the epistemic hegemony of the English language and its detrimental effects on non-English-speaking researchers. Drawing on existing literature, ethical theoretical concepts, and our own experiential knowledge, we illuminate some of the epistemic and linguistic injustices embedded in academic systems. This linguistic domination undermines scholarly credibility, perpetuates exclusion, and affects knowledge production. We integrate thought experiments based on personal experiences to illustrate how this linguistic hegemony penalizes those compelled to write, present, and publish in a language other than their mother tongue. Such practices heighten feelings of shame, erode self-confidence, and restrict access to funding, honours, and reputable publication venues. We employ Stephanie Nixon’s coin model to underscore how unearned privileges are conferred on native English speakers while non-English-speaking academics face myriad invisible barriers. Although English may serve as a unifying medium, its disproportionate dominance curtails the diversity of perspectives needed to address pressing global crises. Linguistic and epistemic injustices harm not only individual researchers’ careers but also the collective scientific endeavour by excluding vast bodies of knowledge published or shared in other languages. Building on Amano et al., we advocate for multilingual dissemination, conscious engagement with non-English literature, and recognition of non-English-speaking researchers’ contributions. There needs to be broader dialogues aimed at upholding and celebrating linguistic and cultural diversity in research.